(untitled) (Journal of the College of Languages (JCL), 2012)
The present paper aims at presenting a feminist reading of Shamela. It specifically seeks to show how the patriarchal mentality behind Shamela dismembers all aspects of the positive image of the woman in Pamela so that nothing remains in the public mind but the prevalent stereotypical image. The narrative in Pamela draws a positive picture of a truly pure, honest, moral woman; the narrative of Shamela redraws that picture by positing the stereotypical image of the woman as a lascivious temptress, false creature, immoral person, and shameless prostitute. This image is what patriarchy intends to endure as it has invented it long ago so that it continues to maintain its domination of society.